Gerak-Ganda: Sebuah Pemecahan Etis Atas Konsep Pasar - Yustinus Prastowo (Respons: Jurnal Etika Sosial, 2010)
Selain gagasan ketertanaman ekonomi dalam konteks sosial, Karl Polanyidikenal luas melalui gagasannya mengenai gerak-ganda. Gagasan ini menekankanbahwa di balik perkembangan liberalisme ekonomi terdapat proteksi sosial sebagaisebuah gerakan positif untuk melindungi masyarakat dari sistem ekonomi apa punyang disruptif. Artikel ini bertujuan untuk menyajikan tesis ini dalam 3 tahap, yakni:konteks sosial munculnya The Great Transformation, gagasan gerak-ganda itu sendiri,dan relevansinya dalam konteks globalisasi ekonomi. Beside the concept of embedded economy, Karl Polanyi is well known throughhis concept of double-movement. The concept emphasizes that behind the progress of economicliberalism emerges the social protection as the positive movement. This movementimplies that society has its collective self-rule and decision makingthat will protect itselffrom all disruptive economic system. This article aims to extend this thesis into three stagesthat are: historical background the Great Transformation, the idea of double-movement,and its relevance in the new context of economic globalization.